Dramatherapy with Women Survivors of Domestic Abuse: A Small Scale Research Study. Issue 1 (March 2015) - Campbell Kirk, Jennifer
The aim of this inquiry was to ascertain the efficacy of a multi-modal model of short-term dramatherapy with women who had suffered domestic abuse. A small-scale study was carried out to compare women who received individual dramatherapy with women who received individual key worker intervention. The 15 women were assigned to either the experimental or the control group. The experimental group received up to 12 weekly dramatherapy sessions with a qualified dramatherapist and the control group received 12 weekly key worker sessions with an experienced domestic violence substance misuse worker. The CORE system was used for both groups to provide pre- and post-intervention scores to assess change. The findings from this study revealed that the women who received dramatherapy presented significant improvements in their CORE Outcome Measure (CORE-OM) scores compared to women who attended key worker sessions. Women in the control group also showed improvements but not to the same extent.